Evaluation of long term outcome of congenital diaphragmatic hernia survivors: a single centre 8 years’ experience in a developing nation with limited facilities - Vageriya, Natasha L.; Shah, Rasik; Mane, Shivaji B.; Daginawala, Taha; More, Prathamesh (International Surgery Journal, 2020)
Background: The objective of the study was to find out incidence of long term complications in congenital diaphragmatic hernia (CDH) survivors in a developing nation with limited facilities. Methods: A retrospective study was done on patients who underwent CDH repair at our institution from 2012 to 2019. 71 patients were identified of these 55 patients operated in neonatal age were considered. After applying exclusion criteria 42 patients included in the study were then divided in 2 groups. Group 1 (26 patients): neonates requiring ventilation within 6 hrs of birth and group 2 (16 patients): not requiring ventilation or intubated after 6hrs of birth. Data from medical records were supplemented by a questionnaire regarding perceived physical function and medical follow up till date. Respiratory, central nervous, musculoskeletal and gastrointestinal systems were concentrated upon and questionnaire set. These were then compared with respect to their long term outcomes. Also, overall incidence of these in the two groups combined was noted compared with other studies. Results: On comparing these 2 groups incidence of long term complications was found more in group 1; however on statistical analysis difference was not significant. As also incidence of individual long term complications in all patients together were identical or lower than in other published series. Mortality in our study was 8 of 49 neonates which was 17% of all patients presenting with CDH or born at our centre. Conclusions: Despite the growing population of CDH survivors the morbidity is not very significant and most patients lead a normal average active life.